2021
DOI: 10.1590/0034-7167-2020-0594
|View full text |Cite
|
Sign up to set email alerts
|

The nurse’s work in the context of COVID-19 pandemic

Abstract: Objective: Reflect on the work experienced by the nurse in coping with the COVID-19 pandemic in a public hospital of the State of Rio Grande do Norte. Methods: Reflective essay based in the professional experience in a public reference hospital for the care of patients affected by COVID-19 in the State of Rio Grande do Norte. Results were organized in two empirical categories, which emphasize potentialities and barriers in the nurse’s work in the face of the COVID-19, presented by means of Ishikawa diagram. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 5 publications
0
7
0
12
Order By: Relevance
“…A Brazilian study whose objective was to reflect on the work experienced by nurses in dealing with the COVID-19 pandemic in a public hospital indicated that despite the various barriers: emotional commitment, fear of contagion, lack of human resources and personal protection elements, the nurses were able to practice with satisfaction and leadership, contributing to the improvement of public health. (28) The experience was an opportunity for personal and professional growth and encountering the essence of nursing. This study also provides relevant information about what could help improve students' teaching/ learning process.…”
Section: Discussionmentioning
confidence: 99%
“…A Brazilian study whose objective was to reflect on the work experienced by nurses in dealing with the COVID-19 pandemic in a public hospital indicated that despite the various barriers: emotional commitment, fear of contagion, lack of human resources and personal protection elements, the nurses were able to practice with satisfaction and leadership, contributing to the improvement of public health. (28) The experience was an opportunity for personal and professional growth and encountering the essence of nursing. This study also provides relevant information about what could help improve students' teaching/ learning process.…”
Section: Discussionmentioning
confidence: 99%
“…In the structuring of these new care sectors, the role of nurses in the organization of the front line of services and in the exercise of care management was evidenced, through forecast and provision of physical, material and human resources necessary to ensure safe care to patients (7)(8)14) . Thus, the importance of the managerial dimension of nurses' work is reinforced, even in a scenario marked by crises and adverse situations with the advent of the COVID-19 pandemic.…”
Section: Changes Implemented In the Work Environment Of Nurses In The Covid-19 Pandemicmentioning
confidence: 99%
“…However, the articulation of the research results in the practice has been a major controversial point; according to López & Barreras 8 , in the current Nursing clinical practice it is acknowledged that, despite the efforts, knowledge translation is an exercise that is seldom contemplated, leading to fragmentation in the implementation of the research results, generating problems for knowledge development, loss in positioning, invisibility of the work performed, invalidity of the results' current nature, and limited impact on the clinical settings. In the light of reality, this paradigm requires an 3/3 urgent intervention from a critical, reflective and visionary perspective which ensures coherent actions since, to permeate the practice, the requirements encompass from an epistemological and historical analysis of the conception to its very conceptualization 9 .…”
Section: Which Changes and Adaptations Must Undergo Nursing To Generate New Evidence In Sindemic And Post-pandemic Settings?mentioning
confidence: 99%